DESKRIPSI TEKANAN DARAH PADA WANITA USIA 60-80 TAHUN PADA LEMBAGA SENAM THERAPY CAKRA WIWEKA SURABAYA - Prasetyo, Alika Heru (Jurnal Kesehatan Olahraga, 2019)
Abstract Naturally the elderly will experience a decrease in organ function and liver blood pressure that is the blood pressure is not constant, changeable and unbalanced. Therefore, the elderly is recommended to always check blood pressure and exercise regularly to prevent disease. Regular exercise can be done by physical exercise in accordance with the elderly such as respiratory exercise or Gymnastics Therapy Cakra Wiweka. This study aims to find out how much influence the Therapy Cervical Therapy Wiweka to decrease blood pressure in women aged 60-80 years of hypertensive patients at Therapy Institute Cakra Wiweka Surabaya. This study used a sample of women aged 60-80 years who suffer from hypertension. In this study, data retrieval is done for 3 months in January, February and March 2018. The data can be based on the results of tests conducted by Healthy Therapy Gymnastics Institute staff Cakra Wiweka Surabaya. So based on the results show the influence / difference each month by following the Healthy Gymnastic Therapy Cakra Wiweka. This blood pressure test was conducted in January because of a gymnastics holiday in December and starting in January, as for taking blood pressure test taken before doing Healthy Gymnastic Therapy Cakra Wiweka.. Keywords: Cakra Wiweka gymnastics, decreased blood pressure, women aged 60-80 years